Étude typo-chronologique des terres cuites architecturales antiques de Châteaubleau (Seine-et-Marne) et de ses environs - Régis Bontrond (Revue Archéologique du Centre de la France)
A systematic study of all the architectural terracottas collected during multiple archaeological excavations on the ancient Châteaubleau urban area was undertaken from the early 2000s. This has enabled the development of a typology of different elements and thus to observe their evolution during the Gallo-Roman period. The data are given in context on a larger scale to compare local trends with those identified by other researchers. Finally, the study opens perspectives on the dating of specific contexts of discovery and more generally on the evolution of different parts of the city.